A SURVEY ON THE RESOURCE-CONSTRAINED PROJECT SCHEDULING PROBLEM - (:unkn) unknown (CHAPMAN HALL LTD, 1995)
In this paper, research on the resource-constrained project scheduling problem is classified according to specified objectives and constraints. Each classified area is extensively surveyed, and special emphasis is given to trends in recent research. Specific papers involving nonrenewable resource constraints and time/cost-based objectives are discussed in detail because they present models that are close representations of real-world problems. The difficulty of solving such complex models by optimization techniques is noted. For the purposes of this survey, a set of 78 optimally solved test problems from the literature and a second set of 110 benchmark problems have been subjected to analysis with some well-known dispatching rules and a scheduling algorithm that consists of a decision-making process utilizing the problem constraints as a base of selection. The computational results are reported and discussed in the text. Constructive scheduling algorithms that are directly based on the problem constraints and whose performances are independent of problem characteristics are identified as a promising area for future research.
Keywords: NET PRESENT VALUE; COST TRADE-OFFS; CASH FLOWS; HEURISTIC PERFORMANCE; PROGRAMMING APPROACH; MULTIPLE RESOURCE; RESTRICTIONS; MAXIMIZE; BRANCH; TARDY